2019
DOI: 10.2174/1573396315666181130144925
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Outcome of Infants with NEC

Abstract: : Necrotizing enterocolitis (NEC) is an important complication for premature newborns. Infants who survive NEC have a greater possibility of poor long-term physiological and neurodevelopmental growth. : The objective of this paper is to give a comprehensive description of the long-term consequences of NEC. Despite the rise in incidence of NEC there is a scarcity of data regarding long-term outcomes of these infants that can be divided into two groups. The first group includes gastrointestinal complications t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Late-onset sepsis (LOS) and necrotising enterocolitis (NEC ≥stage II) contribute to significant mortality and morbidity, including long-term growth and neurodevelopment in preterm infants, especially those born before 28 weeks' gestation. [1][2][3] Recently, NEC and LOS have been shown to be preceded by gut dysbiosis. [4][5][6] Preterm infants are at a high risk of gut dysbiosis due to gut immaturity further complicated by environmental exposures (eg, mode of delivery, chorioamnionitis and neonatal intensive care), feeding intolerance and antibiotic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Late-onset sepsis (LOS) and necrotising enterocolitis (NEC ≥stage II) contribute to significant mortality and morbidity, including long-term growth and neurodevelopment in preterm infants, especially those born before 28 weeks' gestation. [1][2][3] Recently, NEC and LOS have been shown to be preceded by gut dysbiosis. [4][5][6] Preterm infants are at a high risk of gut dysbiosis due to gut immaturity further complicated by environmental exposures (eg, mode of delivery, chorioamnionitis and neonatal intensive care), feeding intolerance and antibiotic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…One study detected a significant influence of all types of nosocomial infections on neurodevelopmental outcomes [8], while another study found a higher risk of cerebral palsy only in infants with Gram-positive nosocomial infections at 2 years of corrected age [23]. As for NEC, multiple studies have reported a strong association with adverse neurodevelopmental outcomes, particularly cerebral palsy [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The variables were selected using previous reports of factors associated with subsequent body composition. [33][34][35][36][37][38][39][40] LCC is a form of hypotension that occurs after the early neonatal period with unclear underlying pathology that is common in Japan but not widely known in North America or Europe. 41 We calculated BMI at ages 18 months and 36 months using weight and height.…”
Section: Data Collectionmentioning
confidence: 99%
“…Gestational age was rescaled so that a value of 0 corresponded to gestational age 23 weeks so that the intercept term measured the BMI for an infant born without IUGR at gestational age 23 weeks. Parity, complications during pregnancy, and hospital stay, which were reported in previous studies [33][34][35][36][37][38][39][40] to be associated with subsequent outcomes, were included as covariates. A backward stepwise model-building method was used to remove nonsignificant covariates.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%